Fungemia and necrotic lymph node infection with Sporopachydermia cereana in a patient with acute myeloid leukemia. (August 2017) - Kingston, Craig; Medinger, Michael; Banderet-Uglioni, Florian; Bassetti, Stefano; Bargetzi, Mario; Haubitz, Sebastian; Fux, Christoph A.; Bättig, Veronika; Goldenberger, Daniel; Passweg, Jakob; Heizmann, Marc
Highlights: Sporopachydermia cereana is a rare yeast. Treatment of the yeast is complicated by difficulties in identification of the pathogen with conventional diagnostic techniques and by intrinsic resistance to echinocandins. The case of the first patient to survive a disseminated infection with S. cereana, who had acute myeloid leukemia, is presented herein. Abstract: Sporopachydermia cereana is a rare yeast found in necrotic cactus tissue, predominantly in the Americas. Infection in humans with clinical data has only been reported in four patients so far, all of whom died, either directly from the pathogen or from other complications of immunosuppression. Treatment of the yeast is complicated by difficulties in identification of the pathogen with conventional diagnostic techniques and by intrinsic resistance to echinocandins. The first patient to survive a disseminated infection with S. cereana is presented herein. The patient had acute myeloid leukemia and was treated successfully with antifungal therapy and subsequently underwent a successful allogeneic hematopoietic stem cell transplantation.